Desenvolvimento de filtros cerâmicos impregnados com nanopartículas de prata para desinfecção de água potável - Cabala, Guillermo Van Erven (2013)
Brazil has vast amounts of hydric resources, whose quality has been deteriorating due to pollutant dumping. Household waste disposal is one of the main sources of water pollution, stimulating bacteria proliferation and introducing microorganisms, including those from fecal matter. Conventional water disinfection methods are a solution, but on the downside, they lead to the formation byproducts hazardous to human health. In this study, aiming to develop bactericidal filters for the disinfection of drinking water; silver nanoparticles were deposited on alumina foams through three routes: sputtering DC, dip coating and in situ chemical reduction of silver nitrate. The depositions were characterized through X-ray diffraction, scanning electron microscopy and EDS element mapping. The influence of the depositions on permeability and mechanical properties of the ceramic foams was assessed and, in sequence, a preliminary antibacterial efficiency analysis was carried out. Characterization results indicate that the chemical reduction routes were efficient in depositing homogeneously distributed silver particles and that the concentration of the metallic precursor salt affects size and morphology of the particles. The antibacterial efficiency analysis indicates that the chemical reduction filters have potential for water disinfection